Enhancing Students’ Reading Comprehension Through Jigsaw - dwiniasih, dwiniasih; Nugraha, Arifial Fahla (Universitas Swadaya Gunung Jati, 2019)
This article mainly describes the use of jigsaw as one the collaborative learning strategies in learning that could foster students’ reading comprehension. It is assumed that Jigsaw could enhance students’ achievement in reading skill. Therefore, test and questionnaire were used in this research to investigate the effect of Jigsaw and students’ response towards Jigsaw applied by the teacher. Finally, Jigsaw implicates students’ achievement become better and it forces students to be a ‘teacher’ speaking up their idea to the other group